Possible dispersal of the coastal and subterranean carabid beetle Thalassoduvalius masidai (Coleoptera) by ocean currents. (10th December 2021) - Nakahama, Naoyuki; Okano, Ryosuke; Nishimoto, Yuichiro; Matsuo, Ayumi; Ito, Noboru; Suyama, Yoshihisa
Abstract: The spatial genetic structures of insects are reflected in their habitats. Coastal insects tend to have less genetic differentiation than subterranean insects. However, the general pattern of population structure of coastal species residing in subterranean habitats is unknown. Thalassoduvalius masidai (Coleoptera: Carabidae: Trechinae), endemic to Japan, is a coastal and subterranean beetle. Here, we hypothesized that T. masidai populations disperse among regions by ocean currents, floods and tsunamis, despite their habitat being underground. To test this hypothesis, we performed a phylogeographical analysis of T. masidai using single nucleotide polymorphism data from multiplexed inter-simple sequence repeat genotyping by sequencing (MIG-seq) and the mitochondrial COI gene. The phylogenetic network and tree and STRUCTURE analyses indicated that T. masidai populations were divided into three groups: the western Seto Inland Sea–Izu Peninsula coasts, the eastern Seto Inland Sea–Kii Peninsula coasts and the Japan Sea coasts. The genetic diversity of T. masidai was higher in sites with lower longitude and latitude. These results suggest that T. masidai migrated and dispersed from the south-western area of Japan by ocean currents, despite its underground habitat. The genetic analysis data from the present study would also be helpful for the conservation and taxonomic revision of this species.